If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 1) + (x + 2) + (x + 3) + (x + 4) = 0 Reorder the terms: x + (1 + x) + (x + 2) + (x + 3) + (x + 4) = 0 Remove parenthesis around (1 + x) x + 1 + x + (x + 2) + (x + 3) + (x + 4) = 0 Reorder the terms: x + 1 + x + (2 + x) + (x + 3) + (x + 4) = 0 Remove parenthesis around (2 + x) x + 1 + x + 2 + x + (x + 3) + (x + 4) = 0 Reorder the terms: x + 1 + x + 2 + x + (3 + x) + (x + 4) = 0 Remove parenthesis around (3 + x) x + 1 + x + 2 + x + 3 + x + (x + 4) = 0 Reorder the terms: x + 1 + x + 2 + x + 3 + x + (4 + x) = 0 Remove parenthesis around (4 + x) x + 1 + x + 2 + x + 3 + x + 4 + x = 0 Reorder the terms: 1 + 2 + 3 + 4 + x + x + x + x + x = 0 Combine like terms: 1 + 2 = 3 3 + 3 + 4 + x + x + x + x + x = 0 Combine like terms: 3 + 3 = 6 6 + 4 + x + x + x + x + x = 0 Combine like terms: 6 + 4 = 10 10 + x + x + x + x + x = 0 Combine like terms: x + x = 2x 10 + 2x + x + x + x = 0 Combine like terms: 2x + x = 3x 10 + 3x + x + x = 0 Combine like terms: 3x + x = 4x 10 + 4x + x = 0 Combine like terms: 4x + x = 5x 10 + 5x = 0 Solving 10 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = 0 + -10 5x = 0 + -10 Combine like terms: 0 + -10 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| 6r-5r=14 | | 10x/x | | x(3x-4)-7=0 | | 8(x-1)(3x-1)=0 | | 250+0.08=410 | | 2(2x+3)-7x=-5(x+3x) | | (x+4)(x-12)-5x=0 | | 9*2x=10(x+8) | | 112=4+96x-16x^2 | | 4x-4=-46-3x | | 6(a1/2)-7 | | 5x-2(3x+4)=-20 | | 6.8c+5=25.4 | | 14x/21y | | 6.8c+5=25.5 | | (5x-30)^-4/3 | | 15m-6m=18 | | 10b-2b+2+b-4b= | | 4x+15=15x-62 | | 5x-2(3x+4)=-12 | | 1-2+1-6+1-10= | | 14k-7k=14 | | 5x/72=5/8 | | 10x+25y+5= | | 1/7=8 | | 14m+8=5m-28 | | 5/11÷-30/11 | | 5j-4j=15 | | 6/10=/5 | | =16x^3+12x^2+8x | | 22/30 | | 4(r-3)= |